A Load Estimation Method Based on Surface Crack Distribution Images of Reinforced Concrete Beams - Hongli Ding; Chun Zhang; Yinjie Zhao; Jian Yu (Buildings)
The preliminary assessment of structural status in reinforced concrete (RC) using visual indicators like surface cracks serves as the primary step in formulating maintenance and reinforcement strategies. To enhance the efficiency of load identification and damage assessment, this study proposes a novel method for determining external load levels on RC beams using structural surface crack distribution images. First, crack distribution characteristics are extracted using image segmentation techniques. Subsequently, mechanical responses of the beam under different load levels are acquired through the finite element method (FEM). Then, this study develops a novel correlation index model by analyzing the relationships between crack distribution images and strain distribution images from the FEM, enabling accurate identification of the load level that best matches the actual crack distribution. Finally, a preliminary assessment of the damage state is conducted through elastoplastic analysis of the RC beam under the optimal load level. Verification analysis based on multiple experimental beam datasets under different load levels demonstrates that the mean absolute percentage error of the method is 10.98%, and the damage assessment results are in good agreement with the crack distribution images.